Taking bark off good men - Pennell, Brett ([New South Wales] : The Author, 2016)
Sgt Brett Pennell, or "Fassi" to his mates, reflects upon a 20 year career within the NSW Police Force with the openness and honesty that is breath taking. Although the book is about "Fassi's amazing rise, from knock about tenacious young footballer through to becoming a counter terrorist qualified sniper, his stories and experiences will resonate with anyone who has worn the uniform with pride and passion. Fassi's reflection upon what drove him to choose policing as a career path, why he always felt such an enormous sense of "belonging" to the tribe and how he struggled, often in silence, with the fight of his life will force the reader to chalenge their own perceptions of policing and what we, the community take for granted. Fassi's greatest challenge, losing his sense of "belonging to a special cause" or "lossing his identity" is a situation many other ex triple "0" members, military personnel or even professional sports people have found themselves dealing with. Taking Bark Off Good Men is a must read for anyone who wants to try to understand or appreciate what the honourable and courageous men and women of policing are feeling and experiencing on a daily basis.
Keywords: Pennell, Brett; Police -- New South Wales -- Anecdotes; Police -- New South Wales -- Biography; Australian